Preoperative CT and MRI prediction of non-resectability in patients treated for pseudomyxoma peritonei from mucinous appendiceal neoplasms. Issue 4 (April 2016) - Menassel, B.; Duclos, A.; Passot, G.; Dohan, A.; Payet, C.; Isaac, S.; Valette, P.J.; Glehen, O.; Rousset, P.
Abstract: Aims: To evaluate computed tomography (CT) and magnetic resonance imaging (MRI) findings for sign of hepatoduodenal ligament and small bowel non-resectability in patients with pseudomyxoma peritonei (PMP) and to compare assessments made by the radiologist based on their experiences. Methods: Between January 2009 and June 2014, all consecutive patients with PMP selected for curative surgery were scheduled to undergo CT and MRI examinations within two days of their surgery. Several imaging findings of hepatoduodenal ligament and small bowel involvements were retrospectively evaluated by a senior and a junior radiologist and compared with surgical findings. Results: Of the 82 patients enrolled in the study, 11 had non-resectable lesions with hepatoduodenal ligament infiltration (n = 4) and/or extensive small bowel involvement (n = 9). All patients underwent CT and 73 underwent MRI scan. Infiltration of the adipose tissue of the hepatoduodenal ligament by mucinous tumor was associated with non-resectability. For the senior and junior radiologists, the sensitivity and specificity were 75% and 100%, and 50% and 100% on CT (kappa value (k) = 0.79); 67% and 100%, and 33% and 97% on MRI (k = 0.38), respectively. Diffuse involvement of the mesentery and/or the small bowel serosa was also associated with non-resectability. For the senior and junior radiologists, the sensitivity and specificity were 67% and 100%, and 56% and 99% on CT (k = 0.82); 88% and 100%, and 38% and 100% on MRI (k = 0.58), respectively. Conclusion: CT and MRI can both contribute to the diagnosis of non-resectability in patients with PMP. The use of MRI to identify small bowel involvement, in particular, benefits from a more experienced radiologist.